Preparation and purification of organic samples for selenium isotope studies. - Helena Banning; Monika Stelling; Stephan König; Ronny Schoenberg; Thomas Neumann (PLoS ONE, 2018)
Selenium (Se) is an important micronutrient but also a strong toxin with a narrow tolerance range for many organisms. As such, a globally heterogeneous Se distribution in soils is responsible for various disease patterns (i.e. Se excess and deficiency) and environmental problems, whereby plants play a key role for the Se entrance into the biosphere. Selenium isotope variations were proved to be a powerful tracer for redox processes and are therefore promising for the exploration of the species dependent Se metabolism in plants and the Se cycling within the Critical Zone. Plant cultivation setups enable systematic controlled investigations, but samples derived from them-plant tissue and phytoagar-are particularly challenging and require specific preparation and purification steps to ensure precise and valid Se isotope analytics performed with HG-MC-ICP-MS. In this study, different methods for the entire process from solid tissue preparation to Se isotope measurements were tested, optimized and validated. A particular microwave digestion procedure for plant tissue and a vacuum filtration method for phytoagar led to full Se recoveries, whereby unfavorable organic residues were reduced to a minimum. Three purification methods predominantly described in the literature were systematically tested with pure Se solution, high concentrated multi-element standard solution as well as plant and phytoagar as target matrices. All these methods efficiently remove critical matrix elements, but differ in Se recovery and organic residues. Validation tests doping Se-free plant material and phytoagar with a reference material of known Se isotope composition revealed the high impact of organic residues on the accuracy of MC-ICP-MS measurements. Only the purification method with no detectable organic residues, hydride generation and trapping, results in valid mass bias correction for plant samples with an average deviation to true δ82/76Se values of 0.2 ‰ and a reproducibility (2 SD) of ± 0.2 ‰. For phytoagar this test yields a higher deviation of 1.1 ‰ from the true value and a 2 SD of ± 0.1 ‰. The application of the developed methods to cultivated plants shows sufficient accuracy and precision and is a promising approach to resolve plant internal Se isotope fractionations, for which respective δ82/76Se values of +2.3 to +3.5 ‰ for selenate and +1.2 to +1.9 ‰ for selenite were obtained.